PENGARUH POLA ASUH ORANG TUA DAN SIKAP BAHASA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN - Santosa, Arif Ismail; Rafli, Zainal; Lustyantie, Ninuk (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study is aimed to determine: (1) the influence of parenting style  and language attitudes  toward  the  reading  comprehension achievement simultaneously; (2) the influence of parenting style and language attitude  toward the reading comprehesion achievement  respectively. This research applied a quantitative approach with descriptive method. The data collection used  questionnaires and objective tests. Questionnaires were used to collect the data on parenting style and language attitudes, and the objective tests were  used to collect the data of reading  comprehension  achievement. The samples of this study were 69 people, and the analysis of this study used descriptive statistic namely regression analysis technique. The result of the research showed: (1) there was positive and significant influence of parenting style and language attitude toward reading comprehension achievement of the grade VII students of The State Junior High School 177 Jakarta about 85.5%; (2) there was a positive and significant influence of parenting style toward the reading comprehension achievement about 38.7%, and language attitudes towards reading comprehension achievement was about 10.2%.